LSD1 inhibition suppresses the growth of clear cell renal cell carcinoma via upregulating P21 signaling - Zhu, Liangsong (Acta Pharm Sin B, 2019)
Histone lysine-specific demethylase 1 (LSD1) has been implicated in the disease progression of several types of solid tumors. This study provides the first evidence showing that LSD1 overexpression occurred in 62.6% (224/358) of clear cell renal cell carcinomas (ccRCC). LSD1 expression was associated with the progression of ccRCC, as indicated by TNM stage (P=0.006), especially tumor stage (P=0.017) and lymph node metastasis (P=0.030). High LSD1 expression proved to be an independent prognostic factor for poor overall survival (P<0.001) and recurrence-free survival (P<0.001) of ccRCC patients. We further show that LSD1 inhibition by siRNA knockdown or using the small molecule inhibitor SP2509 suppressed the growth of ccRCC in vitro and in vivo. Mechanistically, inhibition of LSD1 decreased the H3K4 demethylation at the CDKN1A gene promoter, which was associated with P21 upregulation and cell cycle arrest at G1/S in ccRCC cells. Our findings provide new mechanistic insights into the role of LSD1 in ccRCC and suggest the therapeutic potential of LSD1 inhibitors in ccRCC treatment.